Predicción de islas de calor urbano superficial en el Área Metropolitana de Trujillo (2017-2025) – Perú - Huaman Santa Cruz, Aaron Jhonatan (2022)
In this work, land surface temperature (LST) from moderate resolution Imaging Spectroradiometer (MODIS) sensor was used for the estimation data for 2001 to 2016 period. Forecasting of LST and identification of surface urban heat island (SUHI) on the Metropolitan Area of Trujillo (MAT), Peru for 2017-2025 period, it was carried out using the Quantile method and autoregressive integrated moving average (ARIMA). Monthly data between the period 2001and 2016 was used in the model study, which were separated for daytime and nighttime.The SUHI showed and increasing of 0.12oC and 1.65oC for daytime and nighttime, respectively. Results indicate that LST have increasing about 4.1oC for daytime, and 6.08oC for nighttime.